2007
DOI: 10.1097/cji.0b013e318155a0f6
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Vaccination With Tumor Cell Lysate Plus CpG Oligodeoxynucleotides Eradicates Murine Glioblastoma

Abstract: Dendritic cell (DC) vaccines have shown antitumor activity in experimental glioma models and in human glioma patients. The typical approach has been to generate the vaccine ex vivo, by pulsing DCs with tumor lysate or peptides, then administering the DCs back into the patient. This process requires significant expertise and expenses in DC generation. Immature DCs which present antigens to T cells in the absence of appropriate costimulatory signals can lead to induction of immune tolerance. Recent studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…We previously reported that depletion of CD4 + , CD8 + , and NK1.1 + cells abolished cure of brain tumors in mice that were vaccinated with tumor lysate plus CpG ODN s.c. (33). In this study, we found a dramatic increase in these three populations of BILs in mice treated by CpG ODN, consistent with their putative role in immune surveillance of brain tumors that is exacerbated by CpG ODN.…”
Section: Discussionsupporting
confidence: 83%
“…We previously reported that depletion of CD4 + , CD8 + , and NK1.1 + cells abolished cure of brain tumors in mice that were vaccinated with tumor lysate plus CpG ODN s.c. (33). In this study, we found a dramatic increase in these three populations of BILs in mice treated by CpG ODN, consistent with their putative role in immune surveillance of brain tumors that is exacerbated by CpG ODN.…”
Section: Discussionsupporting
confidence: 83%
“…Our studies in murine leukemia and brain glioma models have shown that administration of CpG ODNs induced in vivo activation of DCs to activate NK and T cell-mediated antitumor responses with potent therapeutic efficacy. 45,46 Adding CpG ODN to PBMCs from lymphoma patients induced activation of blood DCs to enhance T-cell and NK-cell function. 47 Besides the immune-enhancing effects, CpG ODNs are stable, chemically well defined, inexpensive, and safe agents with clinical drugs available for studies.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of TAA-based approaches have been reported for DC-based vaccines (20)(21)(22)29), which are very expensive, time consuming, and process intensive. Recently, easy-to-make and inexpensive vaccines using irradiated whole tumor cells or tumor lysate combined with adjuvants have been reported to be promising for various cancers (16,30,31). Here, we report a tumor lysate-based, directly injectable, personalized therapeutic vaccine for B cell lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…However, this comes with a cost, an increased probability of autoimmune cross-reactivity: i.e., the chance that in the presence of potent adjuvants, DCs can get sensitized to other, nontumorigenic self-proteins and cause autoimmune reactions. Nevertheless, lysatebased vaccines are being investigated as a viable immunotherapy approach for a variety of tumors (15)(16)(17)(18), and in several clinical trials no significant autoimmune reactions were observed (15,19). For lymphoma, there are few reports on tumor lysate-pulsed DC vaccines (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%